If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 8x + -1(3x + 7) + -3 = 0 Reorder the terms: 8x + -1(7 + 3x) + -3 = 0 8x + (7 * -1 + 3x * -1) + -3 = 0 8x + (-7 + -3x) + -3 = 0 Reorder the terms: -7 + -3 + 8x + -3x = 0 Combine like terms: -7 + -3 = -10 -10 + 8x + -3x = 0 Combine like terms: 8x + -3x = 5x -10 + 5x = 0 Solving -10 + 5x = 0 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '10' to each side of the equation. -10 + 10 + 5x = 0 + 10 Combine like terms: -10 + 10 = 0 0 + 5x = 0 + 10 5x = 0 + 10 Combine like terms: 0 + 10 = 10 5x = 10 Divide each side by '5'. x = 2 Simplifying x = 2
| 3x^2-200x-3200=0 | | -5y^2-26y+160=0 | | .06*(x+8)=.03*(2x+9)+0.21 | | X*2Y=20 | | -2+5=3x-10 | | 0.014x^2+0.89=0 | | 3c+12=3 | | -5=5-2k | | -n+2x-4-9n-9x-8= | | 1,4=-t/6.5 | | 8=x^2-5x+8 | | 0=16x^2-3+2x | | 73=5v+3 | | 2x-5=y+17 | | 5x-4=5x+31 | | 2x^3+3x^2+6x+9=0 | | 2(x+10)-2=3-2x | | 3(r+n)=5(r-3)+8 | | 30+(-20)+(-23)= | | -6(2t+2)=36 | | 9x^2+8x+16=24x+17 | | y+9=3(x-1) | | 3(f-4)=15 | | 50x=99x | | 9x^2-16x+16=24x+17 | | x-2.7=-6.2 | | 4x-22=5x+41 | | C^3-3c^2-6c+13=0 | | -4x-2=y+2 | | 4x-22=5x+2y | | -10(s+3)=-106 | | x^2+26x+83=0 |